2006
DOI: 10.1002/polb.20735
|View full text |Cite
|
Sign up to set email alerts
|

Two calorimetric glass transitions do not necessarily indicate immiscibility: The case of PEO/PMMA

Abstract: Differential scanning calorimetry has been used to examine blends of a poly(ethylene oxide) (PEO), Mn = 300 g/mol, and a poly(methylmethacrylate) (PMMA), Mn = 10,000 g/mol, across the complete composition range. The relatively low molar mass of the PEO minimizes interference from crystallization. In the midrange of composition, ∼25–70% PEO, two broad, but distinct, glass transitions are resolved. These are interpreted as distinct glass transitions of the two components, as anticipated by the self‐concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
210
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(227 citation statements)
references
References 42 publications
13
210
2
2
Order By: Relevance
“…Qualitatively, these experimental results support the self-concentration idea, in that individual polymer chain dynamics for the blend constituents should depend on the relative concentrations of each of the compo nents in the blend, as discussed in References [28,37] in which concentration dependent results were obtained based on variations in the amounts of each polymer in the blend. This does not mean that similar glass transition temperatures cannot exist for miscible blend components.…”
Section: Miscible Blend Dynamics and Length Scales Of Mixingsupporting
confidence: 65%
“…Qualitatively, these experimental results support the self-concentration idea, in that individual polymer chain dynamics for the blend constituents should depend on the relative concentrations of each of the compo nents in the blend, as discussed in References [28,37] in which concentration dependent results were obtained based on variations in the amounts of each polymer in the blend. This does not mean that similar glass transition temperatures cannot exist for miscible blend components.…”
Section: Miscible Blend Dynamics and Length Scales Of Mixingsupporting
confidence: 65%
“…The T g values of individual blend components are often used as indicators of miscibility. 2 A single intermediate T g is observed in completely miscible blends and inward T g shifts are observed when there is partial miscibility between blend components. Immiscible blends are just mechanical mixtures of the constituent polymers and such blends generally do not show shifts in their T g , but rather reflect the properties of the neat components.…”
Section: Introductionmentioning
confidence: 95%
“…Lodge et al 13 also suggested that the presence of two g T cannot be used as a criterion of immiscibility and semi-miscibility. A local increase in the self-concentration due to chain connectivity of polymers is an intrachain effect.…”
Section: Calculations Of the Glass Transition Temperature Simulatingmentioning
confidence: 99%